PENGEMBANGAN KOMPETENSI APARATUR SIPIL NEGARA PADA BADAN PENELITIAN, PENGEMBANGAN DAN INOVASI DAERAH PROVINSI SULAWESI TENGAH - Dg. Masiga, Muhammad Anshar; Mufti, Muh. Irfan; Kurnia, Intam (Katalogis, 2021)
This research was a descriptive research with a qualitative approach. Qualitative descriptive research is research that aims to describe events and phenomena that occur in the field and present data systematically, factually and accurately about facts or phenomena that occur in the field. Data collection was done throught observation, interview and documentation techniques. Data analysis in this research used three components consisting of data reduction, data presentation and drawing conclusions. The results of this research show that the Development of State Civil Apparatus Competency of Regional Research, Development and Innovation Agency in Central Sulawesi Province used indicators of ability, skills and knowledge and work attitude. The three indicators are not maximized or cannot be implemented properly, where the implementation of the existing employees do not have the appropriate scientific qualifications, the lack of specific training related to research, and various other factors where in other word the development of state civil apparatus competence is stated to be not optimal.